Legal Settlement Mechanisms for the Use of Blank Checks as Collateral in Information Technology-Based Funding Service Agreements (Lembaga Contrarius Indonesia, 2026)
This study aims to examine the most effective dispute resolution strategies when the debtor issues a blank check as collateral in information technology-based funding service agreements. The concept of justice in this case encompasses both the concept of justice within the positivism paradigm and the concept of justice from the natural law perspective. This type of research is normative/doctrinal research. The research focuses on secondary data, which includes both primary and secondary legal materials. The data analysis technique uses qualitative data analysis. The conclusion-drawing technique uses deductive reasoning. Based on the results of this research, the dispute resolution method chosen in the event of a case involving the issuance of blank checks by debtors used as collateral in information technology-based financing agreements is a settlement method through the criminal justice system.